PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPS SISWA KELAS IX. 1 SMPN 1 MANUJU MELALUI PENDEKATAN SCAFFOLDING DENGAN MODEL PROBLEM BASED LEARNING - Nurliah Nurliah (Universitas Negeri Makassar, 2021)
This research is a class action research (Classroom Action Research) with the aim of improving and improving the quality of learning through the Scaffolding approach with the Problem Based Learning model. The research location is at SMPN 1 Manuju which is located on Jl. the Pallangga-Sapaya axis Km. 28 Pattallikang Village, Kec. Manuju Gowa Regency. The research subjects were class IX.1 students registered in the 2019/2020 school year, with a total of 33 students. In this study, activity data and student learning outcomes were obtained using non-test and test techniques. Data collection was carried out using observation sheets, and itemized questions. The results showed that there was an increase in the activity and learning outcomes of class IX students. 1 SMPN 1 Manuju after learning through the Scaffolding approach with the Problem Based Learning model. This is in accordance with the results of observations of teacher and student activities and student learning outcomes from cycle I to cycle II. the increase in activity and student learning outcomes is due to intensive scaffolding from teachers and students as peer tutors in developing the potential that students have in solving problems.